Endoscopic sleeve gastroplasty in the management of weight regain after sleeve gastrectomy - de Moura, Diogo Turiani Hourneaux; Barrichello Jr, Sérgio; de Moura, Eduardo Guimarães Hourneaux; de Souza, Thiago Ferreira; dos Passos Galvão Neto, Manoel; Grecco, Eduardo; Sander, Bruno; Hoff, Anna Carolina; Matz, Felipe; Ramos, Flávio; de Lima, João Henrique Felício; Teixeira, Leonardo; Dib, Victor; Falcão, Marcelo; Potti, Helmut; Baretta, Giorgio; Jirapinyo, Pichamol; Thompson, Christopher C. (Endoscopy, 2020)
Background Sleeve gastrectomy is a well-standardized surgical treatment for obesity. However, rates of weight regain after sleeve gastrectomy in long-term follow-up are relatively high. This multicenter study is the first to evaluate the use of an endoscopic sleeve gastroplasty (ESG) technique for the management of this population.Methods This was a multicenter retrospective study, including patients with weight regain following sleeve gastrectomy who underwent ESG for weight loss. Primary outcomes included absolute weight loss, percent total weight loss (%TWL), change in body mass index (BMI), percent excess weight loss (%EWL) at 6 and 12 months, and safety profile. Clinical success was defined as achieving ≥ 25 % EWL at 1 year, ≤ 5 % serious adverse event (SAE) rate following society-recommended thresholds, and %TWL ≥ 10 %.Results 34 patients underwent ESG after sleeve gastrectomy. Technical success was 100 %. At 1 year, 82.4 % and 100 % of patients achieved ≥ 10 %TWL and ≥ 25 % EWL, respectively. Mean (SD) %TWL was 13.2 % (3.9) and 18.3 % (5.5), and %EWL was 51.9 % (19.1) and 69.9 % (29.9) at 6 months and 1 year, respectively. Mean (SD) %TWL was 14.2 % (12.5), 19.3 % (5.3), 17.5 % (5.2), and 20.4 % (3.3), and %EWL was 88.5 % (52.8), 84.4 % (22.4), 55.4 % (14.8), and 47.8 % (11.2) for BMI categories of overweight and obesity class I, II, and III, respectively, at 1 year. No predictors of success were identified in the multivariable regression analysis. No SAEs were reported.Conclusion ESG appears to be safe and effective in the management of weight regain following sleeve gastrectomy.